THE IMPACT OF SELF-COMPARISON ON WILLINGNESS TO COMMUNICATE IN ENGLISH: A CROSS-CULTURAL STUDY OF KOREAN AND UZBEK ENGLISHMAJORS - Usmonova, Matkhiya (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2025)
The study explores the impact of self-comparison on the willingness to communicate (WTC) in English among Korean and Uzbek English-major university students. The study becomes essential because the learning of a language is increasingly dependent on communication skills, while scholars have not looked into how people compare themselves across different cultural groups. The research adds new information in terms of looking at two distinct education systems in two diverse cultural contexts. The researcher aimed to establish the relationship between self-comparison and WTC and identify whether there are differences in the two groups of participants. The research adopted a quantitative correlational design which included 200 participants who originated from two distinct locations known as Korea and Uzbekistan. Data was gathered by the researcher through developed survey questionnaires that were subsequently analyzed statistically. The results of the study showed that Uzbek students had higher performance compared to Korean students in both self-comparison and willingness to communicate. From the study, it is evident that self-comparison only maintains a minor relationship with willingness to communicate thus showing its impact occurs conditionally. The research results illustrate that language teaching needs cultural and psychological understanding of successful classroom strategies that enable students from various backgrounds to develop their willingness to communicate.